Drug Development Targeting the Glycogen Synthase Kinase-3β (GSK-3β)-Mediated Signal Transduction Pathway: Role of GSK-3β in Adult Brain - Akihiko Takashima (Elsevier, 2009)
Glycogen synthase kinase-3β (GSK-3β) is a constitutively active kinase. Since its activation results in neurofibrillary tangle (NFT) deposits in aged and Alzheimer's disease (AD) brains, GSK-3β may be inhibited under normal conditions but activated under pathological conditions. Given its link to NFT formation, we sought to determine whether GSK-3β exists in the brain as a "pathological time bomb" that promotes disease development. To address this hypothesis, we analyzed GSK-3β heterozygote (GSK+/−) mice, which express GSK-3β at 50% wild-type levels. When tested in the Morris water maze test, GSK+/− mice surprisingly exhibited retrograde amnesia. Further analysis indicated that GSK+/− mice had impaired memory reconsolidation but normal memory consolidation. Therefore, we concluded that GSK-3β activation is required for memory reconsolidation in the adult brain. Keywords:: glycogen synthase kinase-3β (GSK-3β), memory reconsolidation, aging, neurofibrillary tangle (NFT)